Stage-Stratified Analysis of Prognostic Significance of Tumor Size in Patients with Gastric Cancer - Zu, Hongliang (Public Library of Science, 2013)
BACKGROUND: The prognostic significance of tumor size in gastric cancer is not well defined. The objective of this study was to identify the prognostic value of tumor size in patients with gastric cancer. METHODS: We retrospectively reviewed a total of 1800 patients with gastric cancer admitted to our hospital between 1997 and 2007. These patients were divided into two groups according to tumor size: small size group (SSG, tumor ≤5 cm) and large size group (LSG, tumor >5 cm). We compared clinico-pathologic features of the two groups and investigated the prognostic factors by performing univariate, multivariate, and stage- stratified analyses according to tumor size. RESULTS: LSG had more aggressive clinico-pathologic features than SSG. Tumor size was an independent prognostic indicator in patients with gastric cancer. In a stratified-pT, pN, and pTNM analysis, survival of patients with LSG was significantly worse than that of patients with SSG and advanced stage. Tumor size was not a significant predictor of survival in patients with early stage tumors. Large tumor size was associated with shorter survival in patients with stages N0, N1, N2, and N3, and stages I, II, III, and IV. CONCLUSIONS: Tumor size is a simple and practical prognostic factor in patients with gastric cancer. Tumor size could supplement clinical staging in the future.